Economic Study of a Pediatric Tracheostomy Remote Home Monitoring Program (PTRHMP) Compared to Prolonged Hospitalization for Children With Tracheostomy - Adele K. Evans (Laryngoscope Investigative Otolaryngology, 2025)
ABSTRACT Background/Context Home health nursing is considered critical to transition to at‐home care after pediatric tracheostomy. This diminishing resource contributes a barrier to at‐home care. Telemedicine (Bluetooth wireless technology for monitoring vital signs, Wi‐Fi data transfer to a centralized monitoring center for alarm response) could add support for families during this transition. This manuscript compares a retrospective evaluation of observed hospital costs to modeled estimates for a Pediatric Tracheostomy Remote Home Monitoring Program (PTRHMP): equipment alarm monitoring, call‐to‐home confirmation, and a centralized database of critical information for Emergency Medical Services (EMS) dispatch. Key Methods (1) Cost of Care Cohort analysis of in‐patient cost of care for pediatric tracheostomy patients using retrospective chart review. (2) Modeled cost estimates using a financial proforma developed by experts in the field. (3) Comparative Analysis of Cost of Care Cohort versus PTRHMP proforma. (4) Potentially avoidable Adverse Event analysis. Results Thirty‐three candidates met inclusion criteria for the Cost of Care Cohort Analysis. Average LOS was 31.6 days longer than target LOS, was influenced by average number of caregivers (p < 0.0001) and by age at tracheostomy placement (p = 0.038; 1), and averaged ($17,000/day billed, $3000/day payments received) 10 times the cost estimated for the PTRHMP proforma ($285 per patient‐day). Conclusion The widespread adoption of a Pediatric Tracheostomy Remote Home Monitoring Program (PTRHMP) appears to be technologically and financially tenable at one tenth the cost of in‐patient care. Patients under the age of 2 at tracheostomy placement may represent a separate subgroup for analysis. An implementation study is required to determine the level of safety compared to currently available conditions. Level of Evidence 2—Cohort Study.